Implementasi Pembelajaran Berdiferensiasi pada Pembuatan Scrapbook Kolase di Sekolah Dasar - Kartika Ratri, Maha; Indriani, Fitri (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
This research aims to analyze the implementation of differentiated learning on collage scrapbook making at SD Negeri Kotagede 3 in fine arts subjects. The method used is descriptive qualitative method with case study approach. The informants in the study consisted of class 2A students and class 2A teachers. Data collection techniques were observation, interview and documentation. The results showed that the implementation of differentiated learning in making collage scrapbooks by implementing differentiated teaching strategies namely content, process, product and environment. There are several obstacles encountered during the differentiated learning process including difficulties in conducting class conditioning due to the large number of students and insufficient learning time to complete the project. The implementation of differentiated learning has a positive impact on both teachers and students. Learning activities become varied and meaningful